Pedagogical translanguaging and the construction of science knowledge in a multilingual South African classroom: challenging monoglossic/post-colonial orthodoxies. Issue 3 (2nd October 2019) - Probyn, Margie
ABSTRACT: The majority of learners in South African schools are African language speakers, yet the dominance of English in the political economy has meant that schools choose to switch to English medium instruction by Grade 4, before learners have the necessary English proficiency to access the curriculum, with negative effects on learning. This paper outlines South Africa's long engagement with such issues and documents the translanguaging practices of a teacher who breaks the post-colonial monolingual ideologies prevalent in classrooms and engages with learners' linguistic resources to provide access to both science knowledge and English.